The effects of liquid-phase oxidation of multiwall carbon nanotubes on their surface characteristics; IOP Conference Series: Materials Science and Engineering; Vol. 112 : Fundamental Aspects of Rare-earth Elements Mining and Separation and Modern Materials Engineering (REES-2015) - Burmistrov I. N.; Muratov D. S.; Ilinykh I. A.; Kolesnikov E. A.; Godymchuk (Godimchuk) A. Yu. Anna Yuryevna; Kuznetsov D. V. (2016, 2016)
Title screen